Pendidikan Karakter Anak dalam al-Quran Surat al-A’raf Ayat 31-33 - M. Nasir; Muhibbul Subhi; Samwil Samwil; Ismu Ridha; Jerri Gunandar; Agus Pratama; Ikhsan Ikhsan (ISTIFHAM, 2023)
Al-Quran is the word of Allah SWT, which contains various rules and guidelines for human beings that regulate every aspect of life, including children's personalities. One of the letters about children's personalities is the letter al-A'raf, verses 31-33. In that verse, Allah SWT gives a picture to the believers of how to dress, eat, drink, and do vile things. With regard to the verse, the Qur'an provides an in-depth understanding and understanding of the way of dressing, eating, and drinking that the Sharia permits. This discussion aims to find out the interpretation of surah al-A'raf verses 31-33 related to personality and to know the values ​​of education emphasized in verse. Data collection techniques using literature studies. A child's personality is determined by Islamic education in the family by nurturing and guiding because children are born in a state of nature that requires guidance and direction to awaken a child's potential.